Differentiating Gilbert Syndrome from Crigler Najjar Syndrome Type 2 by Phenobarbitone Test - Sinha, R; Dalal, S; Sodhi, K (Journal of Nepal Paediatric Society, 2015)
Gilbert syndrome characterized by jaundice with intermittent elevations of indirect bilirubin, in the absence of haemolysis or underlying liver disease, has both autosomal dominant and recessive inheritance. Crigler-Najjar syndrome type II (CNS2) is a hereditary disorder of bilirubin metabolism characterized by unconjugated hyperbilirubinemia due to reduced and inducible activity of hepatic bilirubin glucuronosyltransferase (GT). We report 20 children between age 5 to 15 years with unconjugated hyperbilirubenemia who were given seven days of oral phenobarbitone (5mg/kg/day) and decrease in level of bilirubin was noted. There was only 30-40% reduction of bilirubin in Crigler Najjar Syndrome Type 2 compared to Gilberts Syndrome in which bilirubin level normalised. This case series highlights the importance of simple test to differentiate these two conditions. This test is also very helpful in a place where enzyme level and mutational study cannot be done. J Nepal Paediatr Soc 2015;35(1):82-84